Competency Development Model: Pedagogics and Professionalism of Islamic Religious Education Teachers - Fiqhi Ifa Afifa; Imam Fatoni (At-Tarbiyat, 2022)
Pedagogic competence and professionalism have a very important role in the learning process, because they are directly related to the learning process and the development of competencies possessed by teachers, namely planning, implementation, and evaluation. The implementation of learning will be successful depending on the plans prepared by the teacher. This study aims to describe; 1. Planning a model for developing pedagogic competence and professionalism of Islamic Religious Education teachers at SMP NU Gendong implementation, 2. Implementation of the model of developing pedagogic competence and professionalism of Islamic Religious Education teachers at NU Gendong Junior High School, 3. Evaluation of the model of developing pedagogic competence and professionalism of Islamic Religious Education teachers at NU Gendong Junior High School. This research uses descriptive qualitative research with a case study research approach. Sources of data obtained from sources, events, documents and archives. The data collection procedure used unstructured interviews, participatory observation, and document analysis. The data analysis process starts from pre-field analysis, data condensation, data presentation, and verification. Checking the validity of the data using source triangulation. The results of this study are: 1. Planning includes the preparation of Pedagogic indicators and professionalism of Islamic Religious Education teachers, 2. Implementation includes listening, participatory observation, and document analysis. The data analysis process starts from pre-field analysis, data condensation, data presentation, and verification. Checking the validity of the data using source triangulation. The results of this study are: 1. Planning includes the preparation of Pedagogic indicators and professionalism of Islamic Religious Education teachers, 2. Implementation includes listening, participatory observation, and document analysis. The data analysis process starts from pre-field analysis, data condensation, data presentation, and verification. Checking the validity of the data using source triangulation. The results of this study are: 1. Planning includes the preparation of Pedagogic indicators and professionalism of Islamic Religious Education teachers, 2. Implementation includes listening,Keywords:Pedagogic Competence, Professionalism of Islamic Religious Education Teachers